Bromodomain and extraterminal domain inhibitor enhances the antitumor effect of imatinib in gastrointestinal stromal tumours. Issue 4 (19th January 2020) - Mu, Jianfeng; Sun, Pengfei; Ma, Zhiming; Sun, Pengda
Abstract: In gastrointestinal stromal tumours (GISTs), the function of bromodomain‐containing 4 (BRD4) remains underexplored. BRD4 mRNA abundance was quantified in GISTs. In the current study, we investigated the role of BRD4 in GISTs. Our results show a significant enhancement in BRD4 mRNA and a shift from very low‐risk/low‐risk to high‐risk levels as per NCCN specifications. Overexpression of BRD4 correlated with unfavourable genotype, nongastric location, enhanced risk and decreased disease‐free survival, which were predicted independently. Knockout of BRD4 in vitro suppressed KIT expression, which led to inactivation of the KIT/PI3K/AKT/mTOR pathway, impeded migration and cell growth and made the resistant GIST cells sensitive to imatinib. The expression of KIT was repressed by a BRD4 inhibitor JQ1, which also induced myristoylated‐AKT‐suppressible caspases 3 and 9 activities, induced LC3‐II, exhibited dose‐dependent therapeutic synergy with imatinib and attenuated the activation of the PI3K/AKT/mTOR pathway. In comparison with their single therapy, the combination of JQ1/imatinib more efficiently suppressed the growth of xenografts and exhibited a reduction in KIT phosphorylation, a decrease in Ki‐67 and in the levels of phosphorylated PI3K/AKT/mTOR and enhanced TUNEL staining. Thus, we characterized the biological, prognostic and therapeutic implications of overexpressed BRD4 in GIST and observed that JQ1 suppresses KIT transactivation and nullifies the activation of PI3K/AKT/mTOR, providing a potential strategy for treating imatinib‐resistant GIST through dual blockade of KIT and BRD4.